Clinical independent prognostic factors and overall survival prognostic nomogram for intracranial subependymoma: A SEER population-based analysis 2004–2016 - Zhang, Zibin; Pang, Xiaojun; Wei, Yuyu; Lv, Qingping; Jin, Xuhong; Chen, Huai (Frontiers in Oncology, 2022)
Purpose: This study was launched to ascertain the independent prognostic factors influencing the overall survival (OS) prognosis of intracranial subependymoma and construct a prognostic model to predict OS time. Materials and Methods: The patients with intracranial subependymoma were harvested data including the treatment, follow-up data, clinical and pathological characteristics from the SEER database within 2004 to 2016 and randomly disassembled into training and validation cohorts. Univariate and multivariate analyses were applied to the training group through building Cox proportional hazards model. According to the results of multivariate analysis, we established a nomogram to forecast the OS rate of the per-case patient graphically, then calculated the accuracy of verification in both training and validation cohorts by concordance index (C-index). Univariate and multivariate analyses were used for different subgroups of unoperated versus operated, gross total resection (GTR), subtotal resection (STR) and biopsy after using the propensity score matching (PSM) analyses. Results: The 667 patients were finally enrolled, randomly disassembled 535 patients (80.21%) into training and 132 patients (19.79%) into validation cohorts. Age (hazard ratio (HR) = 6.355; 95% confidence interval (CI), 2.240-18.029; P = 0.001) and sex (HR =0.475; 95% CI, 0.232-0.974; P = 0.042) were the independent prognostic factors in the training cohort. On the basis of age and sex, the nomogram was established to predict the OS for every patient (C-index = 0.733 ± 0.065 in the training cohort and 0.850 ± 0.065 in the validation cohort), and calibration plots reflected the reliability of the nomogram. Age, gender or laterality was the independent prognostic factor for OS in the different matched subgroups of unoperated versus operated, GTR, STR and biopsy. Surgical treatment, race, year of diagnosis, insurance, tumor location, tumor size, pathology, tumor grade and radiation were no statistically significant differences in OS for subependymoma in our research. Conclusion: Age and sex were the independent prognostic variables for OS in intracranial subependymoma. According to our research, we should not be more inclined to choose conservative or surgical treatment. Nonetheless, the information that ours present might be useful to suggest potential hypotheses to be tested in the clinical research setting.